A study of cyclonic activity in the North Atlantic for the 2005 versus 2020 season - Hernández Ayala, José J.; Méndez Tejeda, Rafael (Asociación Española de Climatología, 2022)
Ponencia presentada en: XII Congreso de la Asociación Española de Climatología celebrado en Santiago de Compostela entre el 19 y el 21 de octubre de 2022. Over the last two decades, the North Atlantic ocean basin has experienced record-breaking hurricane seasons with regards to storm frequency and intensity. This short study examines the ocean and atmospheric characteristics of the two most active hurricane seasons on record, the 2005 and 2020 seasons. Accumulated cyclone energy, sea surface temperature, sea-level pressure and wind shear data in the main development region of the North Atlantic are compared between the two record-breaking seasons. Results of time series analysis show that 2005 was the hurricane season with the highest accumulated cyclone energy index, while 2020 was the 4th highest of 55 seasons analyzed. Results of spatial analysis of sea surface temperature anomalies exhibit that 2005 had a slightly higher average surface temperature than 2020 in the main development region of tropical cyclones, and that 2005 had higher temperatures in the central region of the study area while 2020 had higher surface temperatures in the southern Caribbean region. Comparisons between the sea level pressure anomalies show that 2005 had a slightly lower average pressure than 2020, with 2005 exhibiting lower anomalies in the northern area and 2020 showing anomalous pressure patterns in the eastern part of the main development region. When wind shear anomalies are examined, we found that 2020 had a lower average wind shear than 2005, a factor that could explain why 2020 had a higher number of tropical cyclones. Overall our results suggest that both 2005 and 2020 seasons had similar ideal ocean-atmospheric conditions for higher tropical cyclone activity.